Ecological Education in a Personalistic Perspective - Dziekoński, Stanisław (Studia Ecologiae et Bioethicae, 2003)
In the modern world, the value and the dignity of man, the value of life are very often placed in doubt, while consumer mentality, the glorification of freedom, subjection to egoism - achieve great measures. This situation has its negative reflection on education towards the respect of the socio-natural environment. Suggestions presented for pro-ecological education quite frequently concentrate on practical recommendations, which apply above all to the world of nature. Many a time the social dimension of this education and personalistic motivation are omitted. So, the uncovering of the value of pedagogical personalism for ecological education is especially important today. The reflection presented here shows that ecological education is close to the personalistic concept of education, and it is even immanently rooted in the aims and principles plotted by it. At the foundations of ecological education in personalism, we find the greatness and the dignity of the human being as a person. The .personalistic norm.) of pro-ecological education by no means depreciates other beings possessing autonomy and objective value. Between man and other beings, one can see close ties, relations of interdependence, common sharing of destiny. This is especially underlined in the Christian concept of personalism, which directs the whole of education in the Christ-centered direction.